«La política es winka, la historia es mapuche». Alleanze, conflitti e trasformazioni all’interno della pratica politica mapuche - Olivia Casagrande (EtnoAntropologia, 2016)
The struggles for the land of the '70s saw the alliance between the Mapuche communities and the Chilean left in a "class struggle" in which the indigenous society was included within the general category of campesinos. This process was brutally interrupted by the coup of Pinochet, whose violent repression has contributed to reshape the contraposition according to the previous axis Mapuche-winka (non-Mapuche). Also as a consequence of these tensions, the current Mapuche movement is based on the ideas of self-determination and recovery of the ancestral territory, constituting as a particular "cosmopolitics" that seems to distance itself both from the Western political conception, and from the previous alliance with the Chilean left. The present paper compares the two moments through the analysis of the indigenous leader’s narrative, aiming at understanding the transformations of the Mapuche political practice and its dialectical relationship with the Chilean Other.